Wandering Games - Kagen, Melissa (The MIT Press, 2022)
An analysis of wandering within different game worlds, viewed through the lenses of work, colonialism, gender, and death. Wandering in games can be a theme, a formal mode, an aesthetic metaphor, or a player action. It can mean walking, escaping, traversing, meandering, or returning. In this book, game studies scholar Melissa Kagen introduces the concept of "wandering games," exploring the uses of wandering in a variety of game worlds. She shows how the much-derided Walking Simulator-a term that began as an insult, a denigration of games that are less violent, less task-oriented, or less difficult to complete-semi-accidentally tapped into something brilliant: the vast heritage and intellectual history of the concept of walking in fiction, philosophy, pilgrimage, performance, and protest. Kagen examines wandering in a series of games that vary widely in terms of genre, mechanics, themes, player base, studio size, and funding, giving close readings to Return of the Obra Dinn, Eastshade, Ritual of the Moon, 80 Days, Heaven's Vault, Death Stranding, and The Last of Us Part II. Exploring the connotations of wandering within these different game worlds, she considers how ideologies of work, gender, colonialism, and death inflect the ways we wander through digital spaces. Overlapping and intersecting, each provides a multifaceted lens through which to understand what wandering does, lacks, implies, and offers. Kagen's account will attune game designers, players, and scholars to the myriad possibilities of the wandering ludic body.